Normative White Femininity: Race, Gender and the Politics of Beauty - Deliovsky, Kathy (Atlantis, 2008)
This article is an exploration of how racialized beauty norms invoke a cultural discourse of racially coded degrees of femininity and beauty. White patriarchal discourse represents white women as the "Benchmark woman" - a hegemonic ideology and social location that define dominant and subordinated femininities.